(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
This comparative analysis delves into the intricate narratives of Arundhati Roy’s celebratednovels, The God of Small Things and The Ministry of Utmost Happiness, with a focused explorationof women’s place and subjectivity formation within these literary landscapes. It underscores thesignificance of delving into women’s place and subjectivity within her works, considering the broadercontext of gender dynamics in society. Employing feminist literary criticism as its foundation, thisresearch investigates how women characters are portrayed, their societal roles, limitations, and how thesettings influence their subjectivity. It emphasizes the significance of intersectionality in analyzingwomen’s experiences, encompassing factors such as race, class, and other intersecting identities. Itdelves into the role of history, memory, and landscape in shaping women’s identities and experienceswithin these narratives. Furthermore, the analysis examines how patriarchal ideologies are depicted andresisted in both novels, shedding light on the nuanced ways in which gender dynamics are challenged.It synthesizes findings from the comparative analysis, offering key insights into women’s place andsubjectivity in Arundhati Roy’s works. This research contributes to the understanding of Arundhati Roy’sliterary contributions, feminist literary theories, and the broader discourse on gender dynamics inliterature.